Synthesis and characterization of CuGaSe2 nanoparticles prepared by a microwave method - S. Tongpeng (2018)
Copper gallium diselenide (CuGaSe2) nanopowder is a p-type semiconductor potentially for use as a thermoelectric material. Nanoparticles of CuGaSe2 were synthesized by a microwave method using Cu(NO 3)2 • 3H2O, Ga2(SO 4)3 and SeO2as precursors and ethylene glycol as a solvent. A preparative parameter for the synthesis of CuGaSe2 was a pH value, which varied from 5, 6, 7, 8 to 9. The reaction time in the microwave oven was carried out for 50 seconds; stopped for 3 minutes, 17 cycles at a power of 1100 Watts. From the characterization of product powders by X-ray diffraction, scanning electron microscopy and transmission electron microscopy techniques, it was found that CuGaSe2 powder was successfully synthesized at pH 6. The CuGaSe2 phase was observed to occur as the main phase with CuSe contaminant. However, the CuSe impurity was decreased when annealed at 560 °C in a nitrogen gas atmosphere for 1 and 3 hours.